2021
DOI: 10.1016/j.crphar.2020.100013
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of pharmacological manipulations on Arc function

Abstract: Activity-regulated cytoskeleton-associated protein (Arc) is a brain-enriched immediate early gene that regulates important mechanisms implicated in learning and memory. Arc levels are controlled through a balance of induction and degradation in an activity-dependent manner. Arc further undergoes multiple post-translational modifications that regulate its stability, localization and function. Recent studies demonstrate that these features of Arc can be pharmacologically manipulated. In this review, we discuss s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 144 publications
0
7
0
Order By: Relevance
“…Although Arc protein expression is induced in neurons by multiple stimuli [52], only a few studies showed a causal link between Arc expression and animal behavior. In particular, Arc affects memory formation, cognitive exibility, anxiety, cocaine self-administration and schizophrenia-related behaviors [22,[53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Although Arc protein expression is induced in neurons by multiple stimuli [52], only a few studies showed a causal link between Arc expression and animal behavior. In particular, Arc affects memory formation, cognitive exibility, anxiety, cocaine self-administration and schizophrenia-related behaviors [22,[53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…4A and Tables S4, S7). Arc is involved in activity-dependent neuronal plasticity in the brain [76] as well as acute and chronic neuroinflammation [77]. We found no prior reports of Arc function or expression in the retina; yet Arc's upregulation in Müller glia following KCl treatment is consistent with its role in other regions of the CNS.…”
Section: Cell Type-specific Response To Stress Injury and Disease In ...mentioning
confidence: 54%
“…Evidence of involvement of Arc in AD pathology and the role of Arc in regulating learning and memory which are severely disrupted in AD raises the possibility of targeting Arc therapeutically to ameliorate some of these disruptions. Several drugs are known to alter Arc levels and function, including psychotropic drugs as well as other drugs that manipulate the proteasome and the autophagy-lysosome systems, most of which are well-studied and are already in use to treat other disorders ( 103 ). However, given the complexity of the role of Arc in AD, the desired effect of pharmacologically altering Arc remains unclear.…”
Section: Discussionmentioning
confidence: 99%